2015
DOI: 10.1002/app.43126
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly imprinted polymer prepared by Pickering emulsion polymerization for removal of acephate residues from contaminated waters

Abstract: A molecularly imprinted polymer (MIP) prepared with Pickering emulsion polymerization was designed by a computational approach for removal of acephate from aqueous solution. Methacrylic acid, ethylene glycol dimethacrylate, and chloroform were screened as the optimal functional monomer, crosslinker, and porogen by the Gaussian 03 package using the density functional theory method. The polymerization was carried out in an oil-in-water emulsion using nano-SiO 2 particles as stabilizer instead of a toxic surfacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 50 publications
0
13
0
1
Order By: Relevance
“…As mentioned by some authors, the selection of the monomer(s) and the template/monomer(s) ratio can be carried out by studying the changes in UV spectra of the template when adding increasing concentration of the monomer in the solvent selected for the synthesis [67,69,77]. Other spectroscopic methods were used such as NMR to highlight the presence of hydrogen bonds between the template and MAA [39,67,69,72,73] and FT-IR to highlight the interactions between OPP and OH-group of MAA [39,46,55,61,70,76,80,91,97,98,102]. This method was also used to control the template removal by comparing MIP spectrum before and after its washing [64,93,99], this control being most of the time ensured by analyzing the template amount in the washing solution by UV detection or by chromatographic analysis.…”
Section: Synthesis Of Mipsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned by some authors, the selection of the monomer(s) and the template/monomer(s) ratio can be carried out by studying the changes in UV spectra of the template when adding increasing concentration of the monomer in the solvent selected for the synthesis [67,69,77]. Other spectroscopic methods were used such as NMR to highlight the presence of hydrogen bonds between the template and MAA [39,67,69,72,73] and FT-IR to highlight the interactions between OPP and OH-group of MAA [39,46,55,61,70,76,80,91,97,98,102]. This method was also used to control the template removal by comparing MIP spectrum before and after its washing [64,93,99], this control being most of the time ensured by analyzing the template amount in the washing solution by UV detection or by chromatographic analysis.…”
Section: Synthesis Of Mipsmentioning
confidence: 99%
“…Computational design was also proposed to simulate monomer-template interactions and then to select the best monomer, i.e. the monomer that gives the highest interaction energy with the template [39,56,65,67] or to elucidate the best template/monomer ratio [79]. It was reported that results obtained using this approach, despite its high potential, must be confirmed by retention measurements (HPLC, SPE profiles) [56,81] or binding experiments [71] thus implying the synthesis of several MIPs with a selection of templates and/or monomers selected by the simulation.…”
Section: Synthesis Of Mipsmentioning
confidence: 99%
“…The development of MIPs for the extraction of OPs has been largely reported these last years. MIPs were prepared as particles to be used in cartridges between two frits as SPE sorbent [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] or as dispersive sorbent for dSPE [27][28][29][30][31] and for matrix solid-phase dispersion (MSPD) [32][33][34] or as a thin film in solid-phase microextraction (SPME) [35][36][37] or in stir bar sorption extraction (SBSE) [38]. They were applied to the selective extraction of OPs from vegetable extracts (cucumber, lettuce, apple, pear…) and environmental samples such as waters and soil extracts.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the template was studied only once for the development of an MIP for dimethoate and its metabolite omethoate showing that the metabolite was better adapted for the trapping of both molecules [19]. A few studies described the synthesis of an MIP by varying the nature of the monomer [11,19,28,30,31] and/or the porogen [11,25,30,31] or the template/monomer ratio [24]. In some studies, the choice of the monomer for a given template resulted from studies by molecular modeling and computational design [17,19,23].…”
Section: Introductionmentioning
confidence: 99%
“…在生物样本中, 基于Pickering乳液的分子印迹技术也展现出巨大潜 力. 例如, Yang等人 [20] [21] , 我们将近年来已发表的采用Pickering乳液聚 [22,23] 、荧光 [19] 、空心 分子印迹 [22,29] 等)方向发展; (2) 向制备能在复杂样品 体系(如河水 [37,38] 、血液 [39,45] 、尿液 [20,39] [53,54] ; 对于疏水性蛋白质分子, 目前还没有利用Pickering乳液聚合成功合成蛋白质印 迹的报道. 但疏水蛋白具有在亲水-疏水界面通过自 组装形成蛋白膜的重要特性, 自组装的蛋白质颗粒本 身能作为固体颗粒稳定剂制备界面印迹MIP材料 [55] .…”
Section: Pickering乳液聚合制备分子印迹聚合物unclassified